ARAHAN RENCANA DAN STRATEGI PEMANFAATAN RUANG KAWASAN PERI URBAN KOTA MALANG - Permana, Mirza - (Department of Urban and Regional Planning, Faculty of Engineering, Universitas Brawijaya, 2023)
Malang City experienced rapid development as an education city and tourist city. Limited urban space causes the development of the city to lead to the periphery. There are 8 sub-districts in Malang Regency which are directly adjacent to Malang City and have had a significant influence on the development of Malang City. The peri urban area is a transition area between urban and rural areas. This region is slowly undergoing a transformation of space from agriculture to urban activities. This studyÂ aims are to explore the typology of peri-urban areas and to the direction of plans and strategies for spatial use in peri-urban areas. The research method used is spatial data analysis based on land use and image interpretation and the use of Geographic Information System software and Idrisi Selva. The results show that 4 sub-districts characterized by urban and 4 other sub-districts are still characterized by rural areas. From 2008 to 2018, the addition of built-up area increased by 12%. The development of peri-urban areas is influenced by population growth, settlement patterns, good accessibility and availability of socio-economic facilities. The pattern of changes in land use shows that agricultural land, both gardens / fields and dominant paddy fields has changed into a built-up area (8.3%). These agricultural lands are productive agricultural land with a suitability level of S2 dominant land (suitable) 60.4%. The direction of Malang urban peri-urban space use is prioritized to maintain agricultural land in sub-districts with rural typology. This is also supported by expert opinion emphasizing the need to protect agricultural land with preventive efforts. The strategy needed is to limit the urban development area based on the characteristics of the sub-district through a detailed spatial plan.